The Relationship of Leadership Styles and Sustainability: Regression Analysis of the Antecedents in Achieving Sustainable Performance - Ibnu Suryo, Ibnu Suryo; Istiatin, Istiatin; Legowo Dwi Resihono, Legowo Dwi Resihono; Sakidi, Sakidi (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This study examines the relationship between Leadership Styles, including Transformational and Transactional Leadership, and Sustainability. This study also includes other variables, such as Entrepreneurial Orientation and Innovation Capability. This research uses a quantitative approach and 216 data are gathered. The results of this study stated that both leadership styles significantly and positively impact the other three variables. Though both of them have a significant impact, Transformational Leadership mostly has a higher impact than Transactional Leadership. There are two interesting findings in this study. First, the impact of Entrepreneurial Orientation on Innovation Capability is higher in Transactional than in Transformational Leadership. The second finding is that Innovation Capability negatively impacts Sustainable Performance in Transformational Leadership. The discussion, conclusion, limitations, and suggestions are provided in this journal.